Ownership Status of Petok D Land that Has Been Transferred From an Unauthorized Party - Febrianto, Dhean; Setyadji, Sri (Activa Yuris: Jurnal Hukum, 2025)
Letter C and Petok D books, although after the enactment of the UUPA are no longer evidence of land management, PP article 24 no. Article 24 of the Law (1997) further regulates the recognition of the necessity to record land rights as old written evidence. The problem is how the relationship between case decision 190/Pdt.G/2005/PN.Sby with decision no. 94/PDT/2007/PT.SBY with decision No. 2340 K/PDT/2008 with decision No. 233 PK/Pdt/2011 and how the legal status of buyers of land rights petok d. is not eligible. The study used as treatment is a normative legal study based on principles and concepts. Obtained the following research results: Land rights with letter C and Petok D are allowed according to Article 39 of PP. 24 of 1997, but if the letter C and Petok D book are tampered with by changing the name written in it, then it is a prohibited act, and the judge in his opinion canceled the letter C and Petok D book with evidence. Letter C and Book Petok D A seller who does not have the right to sell it and has it canceled by a court judge, can sue the seller on the grounds that he has committed an unlawful act.